Al Kausar Internat SMP Carbon Footprint Modeling Parungkuda District, Sukabumi District, West Java Province - Aris Munandar, Aji Marwonto; Sodikin, Sodikin; Utami, Prasetyarti (Jurnal Multidisiplin Indonesia, 2024)
Carbon Footprint Modeling of Al Kausar Boarding School in the Parungkuda area is the first step in realizing low-carbon educational activities based on boarding school life. This research aims to analyze carbon emissions from the direct and indirect activities of current Al Kausar Internat Middle School residents, as well as develop a model based on a dynamic systems approach to reduce carbon emissions in the future. The research method uses a quantitative approach by collecting data through literature study, observation, questionnaires, interviews, documentation, measuring waste generation, calculating secondary and primary data, calculating gas usage, and calculating the duration of social media access. The research results show that the total carbon emissions from several dominant activities of Al Kausar Boarding School are currently 839,721,408 KgCO 2 eq. Teak gardens and various trees in the school environment absorb carbon dioxide (CO2) as much as 592,675.64 KgCO2 per year. Using carbon uptake by trees cultivated in Al Kausar, total carbon emissions are corrected to 607,888.82 KgCO 2 eq, reducing total emissions to 231,832,588 KgCO 2 eq in scenario I. Scenarios II, III, and IV show further reductions in carbon sequestration from various plants, even reaching harmful total carbon emissions. Scenario V shows an increase in the absorption capacity of trees, which causes total carbon emissions to be corrected to -12,967,412 KgCO 2 eq. Scenario VI shows an increase in the carbon absorption capacity of trees, reducing total carbon emissions to 252,845,358 KgCO 2 eq. With this intervention, it is hoped that Al Kausar Boarding School can become a sustainable education with a lower carbon footprint."